Autoantibody Signature in Cardiac Arrest. Issue 22 (2nd June 2020) - Maguy, Ange; Tardif, Jean-Claude; Busseuil, David; Ribi, Camillo; Li, Jin
Abstract : Background: Cardiac arrest is a tragic event that causes 1 death roughly every 90 seconds worldwide. Survivors generally undergo a workup to identify the cause of arrest. However, 5% to 10% of cardiac arrests remain unexplained. Because cardiac arrhythmias underlie most cardiac arrests and increasing evidence strongly supports the involvement of autoantibodies in arrhythmogenesis, a large-panel autoantibody screening was performed in patients with cardiac arrest. Methods: This is an observational, cross-sectional study of patients from the Montreal Heart Institute hospital cohort, a single-center registry of participants. A peptide microarray was designed to screen for immunoglobulin G targeting epitopes from all known cardiac ion channels with extracellular domains. Plasma samples from 23 patients with unexplained cardiac arrest were compared with those from 22 patients with cardiac arrest cases of ischemic origin and a group of 29 age-, sex-, and body mass index–matched healthy subjects. The false discovery rate, least absolute shrinkage and selection operator logistic regression, and random forest methods were carried out jointly to find significant differential immunoglobulin G responses. Results: The autoantibody against the pore domain of the L-type voltage-gated calcium channel was consistently identified as a biomarker of idiopathic cardiac arrest ( P =0.002; false discovery rate, 0.007; classification accuracies ≥0.83). Functional studies on human induced pluripotent stem cell–derived cardiomyocytes demonstrated that the anti–L-type voltage-gated calcium channel immunoglobulin G purified from patients with idiopathic cardiac arrest is proarrhythmogenic by reducing the action potential duration through calcium channel inhibition. Conclusions: The present report addresses the concept of autoimmunity and cardiac arrest. Hitherto unknown autoantibodies targeting extracellular sequences of cardiac ion channels were detected. Moreover, the study identified an autoantibody signature specific to patients with cardiac arrest. Abstract : Supplemental Digital Content is available in the text.